Peran Teknologi pada Pembelajaran IPS untuk Meningkatkan Kesadaran Siswa Terhadap Isu Global - M.Danish Sumantri; Allyah Zahirah; Bilal Bilal; Sani Safitri (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
The purpose of this study was to determine how technology functions in social studies learning and how technology affects students' awareness of world issues. This study was conducted through a qualitative approach with a case study as its design. The results showed that the use of technology, such as e-learning platforms, social media, and learning applications, significantly increased student engagement in social studies learning. Technology also gives students access to more information about global issues, such as international conflicts, climate change, and social injustice. Thus, students are trained to have analytical thinking skills and are able to understand the relationship between international events and everyday life. By increasing awareness of global issues, it is hoped that students can foster a sense of empathy, social responsibility, and play an active role in solving global challenges. This study found that the use of technology in social studies learning not only improves students' academic understanding but also makes them more involved in global issues as well as more sensitive and understanding in responding to global challenges.